Análise da qualidade de áudio no serviço móvel aeronáutico - Frigotto, Rodrigo Luiz (2018)
From the airplane until reaching air-traffic controllers, transmitted signals that carry audio information may suffer different kinds of degradation. Radio interference, range or canalization issues and the use of compression are among the most common sources of audio degradation in aeronautical communications. In this work it is studied the speech quality in aeronautical communications, using standardized subjective tests applied over signal degradations of normally used aeronautical telecommunication systems of the SISCEAB (Brazilian System of Airspace Control). For this purpose, an audio database was prepared, with reference speech signals being recorded in a professional audio studio. These signals were latter submitted to different degradations of the common means of communication used in airspace control and, next, were evaluated, as standardized in the ITU-T P.800 standard, by human subjects in order to express the MOS, an audio quality index. Latter, these indexes were used to test the performance of two objective analysis algorithms, the PESQ (ITU-T P.862) and the SESQ (ITU-T P.563), in order to verify if they could predict the MOS of signals degraded by the means used in air-traffic control communications. The results show wide variations in the MOS depending on the media used, with marked variation in communications that used radiofrequency. It was also observed that the PESQ showed good performance predicting the MOS of telecommunication systems used in the SISCEAB